Opuntia ficus-indica is an excellent eco-friendly biosorbent for the removal of chromium in leather industry effluents. Issue 6 (June 2021) - Figueirôa, Juliana Andreza; Menezes Novaes, Guilherme Urias; de Souza Gomes, Hélder; de Morais Silva, Vera Lúcia Meira; de Moraes Lucena, Danilo; Lima, Lígia Maria Ribeiro; de Souza, Seldon Almeida; Viana, Lucas Gustavo Ferreira Cordeiro; Rolim, Larissa Araújo; da Silva Almeida, Jackson Roberto Guedes; Oliveira, Ana Paula de; Gomes, Josivanda Palmeira
Abstract: In Brazil, the leather industry is an important economic segment moving around U$ 3 billions of dollars a year. However, high amounts of water are requested to transform skin animals into leather, causing high wastewater amounts to be consequently produced. A major problem is attached to the presence of chromium in the wastewater from the tanning process. Chromium is a heavy metal potentially toxic both to the environment and to the human health. In order to control the levels of chrome dumped into the environment, Brazilian agencies require the treatment of effluents by the generating source. Thus, this study aimed to develop an alternative method to the removal of chromium in wastewater from the leather industry using the Opuntia ficus-indica biomass as eco-friendly biosorbent. Crude waste samples were collected in a tannery stabilization pond for chromium quantification and further treatments. The powdered Opuntia ficus-indica was obtained from species collected in Pernambuco, Brazil, and its physical parameters and pHPCZ were characterized. Adsorptions studies and acute toxicity were also carried out. The biomass remaining after the sorption was analyzed through scanning electron microscopy and Fourier-transform infrared spectroscopy. The chromium content was above the limit allowed by the Brazilian regulatory agency. In sorption studies, biomass was able to remove 74.8% and 84.88% of Cr (III) using 2.0 g and 4.0 g of biomass, respectively. The surface of biomass is very favorable to biosorption and the chemical bindings among oxygen atoms present in the chemical components of this biomass and the heavy metal was confirmed through infrared spectrum. This study proved that Opuntia ficus-indica is effectively biosorbent to chromium, promising and with low costs for the leather industry, able to reduce its ecotoxicity as proven by chemical and biological assays. Abstract : Palma forrageira, Sorption, Chromium, Tannery, Artemia salina, Ecotoxicity, Wastewater treatment.